Evaluation of the use of cold plasma conditions for Fe isotopic analysis via multi-collector ICP-mass spectrometry: effect on spectral interferences and instrumental mass discrimination. Issue 3 (20th February 2017) - Chernonozhkin, Stepan M.; Costas-Rodríguez, Marta; Claeys, Philippe; Vanhaecke, Frank
Abstract : The application of cold plasma conditions for isotopic analysis of Fe via MC-ICP-MS was evaluated in combination with the standard and the 'jet' interface and with dry and wet plasma conditions. Abstract : The advantages and disadvantages of using cold plasma conditions in combination with both the standard and the high-transmission ('jet') plasma interface and under dry and wet plasma conditions were evaluated in the context of high-precision isotopic analysis of Fe via multi-collector inductively coupled plasma-mass spectrometry (MC-ICP-MS). When using the standard interface and wet plasma, cold plasma conditions suppressed the occurrence of the polyatomic ions 40 Ar 14 N + and 40 Ar 16 O +, but not that of 40 Ar 16 O 1 H + . Dry plasma conditions efficiently removed the (hydr)oxide ions, but at the cost of a dramatic increase in the prevalence of 40 Ar 14 N + . Thus, interference-free 56 Fe/ 57 Fe measurement can be performed at low mass resolution using cold plasma conditions and the standard plasma interface. No alleviation of the spectral interferences due to Ar-based ions was observed with the 'jet' interface with cold plasma conditions. With cold plasma conditions, the instrumental mass discrimination affecting the Fe isotope ratios was mitigated compared to that obtained with hot plasma when the standard interface was used (1.4% per amu versus 3.2% per amu, respectively). This mitigation in instrumental mass discrimination with cold plasma conditions was not observed when the high-transmission interface was used.